2015
DOI: 10.4236/jct.2015.64041
|View full text |Cite
|
Sign up to set email alerts
|

Level of Adherence to Cytotoxic Drugs by Breast Cancer Patients’ in Lagos State University Teaching Hospital

Abstract: Background: Breast cancer is one of the most common malignant diseases in women and adjuvant combination chemotherapy has been shown to reduce mortality from this disease. Adherence to medical treatment is a multifaceted issue that can substantially alter the outcomes of therapy. Patient non-adherence to chemotherapy is the ultimate barrier to the treatment effectiveness. Objective: This study was carried out to determine the relationship between cancer chemotherapy adherence and breast cancer staging, patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…A large meta-analysis reported that marital status increased the odds of adherence to treatment by 1.27, reinforcing the significant role that social support mechanisms play in shaping chemotherapy adherence [15]. In Africa, the significance of marital status has been reported [72]. The interplay of marital status and social support seems to favor women in this trial.…”
Section: Discussionmentioning
confidence: 55%
“…A large meta-analysis reported that marital status increased the odds of adherence to treatment by 1.27, reinforcing the significant role that social support mechanisms play in shaping chemotherapy adherence [15]. In Africa, the significance of marital status has been reported [72]. The interplay of marital status and social support seems to favor women in this trial.…”
Section: Discussionmentioning
confidence: 55%
“…Even though not statistically significant, married women in this study had lower odds for advanced staged breast cancer compared to unmarried women While lower SES has been associated with late-stage breast cancer diagnosis in several studies, the only significant effect in the study carried out by Joseph Lipscomb et al was that single women were generally at higher risk to advanced stage than married women, whereas Popoola etal discovered that emotional support is most beneficial in the adjustment of women with breast cancer, generating opportunities for them to express feelings and favoring treatment adherence and spouse has been found out the most important emotional support and the main source of instrumental support [7][8].…”
Section: Discussionmentioning
confidence: 99%